Comparing quality of care for sexually transmitted diseases in specialized and general clinics. - Asch, Steven M. (Association of Schools of Public Health, 2002)
OBJECTIVE: The objective of this study was to compare quality of care for patients with sexually transmitted diseases (STDs) in specialized vs. general clinics. METHODS: The authors conducted a retrospective chart review evaluating compliance with a set of STD-related process of care quality indicators for adult patients seen in six Los Angeles County clinics (two STD specialized clinics and four general medical clinics). RESULTS: Thirty-two quality indicators were selected using a modified Delphi process. From March 1, 1996, to June 31, 1996, there were 205 STD-related visits to the two specialized STD clinics and 373 STD-related visits to the four general medical clinics. For patients with "classic" STDs (those for which sexual contact is the primary means of transmission), STD clinics achieved greater compliance than general medical clinics on 14 quality indicators, while general medical clinics achieved greater compliance on 4 indicators. CONCLUSION: STD clinics provide better overall STD care than general medical clinics. Possible explanations include differences in clinician experience with STD patients and greater use of standardized protocol sheets.